2018
DOI: 10.1093/nar/gky999
|View full text |Cite
|
Sign up to set email alerts
|

Victors: a web-based knowledge base of virulence factors in human and animal pathogens

Abstract: Virulence factors (VFs) are molecules that allow microbial pathogens to overcome host defense mechanisms and cause disease in a host. It is critical to study VFs for better understanding microbial pathogenesis and host defense mechanisms. Victors (http://www.phidias.us/victors) is a novel, manually curated, web-based integrative knowledge base and analysis resource for VFs of pathogens that cause infectious diseases in human and animals. Currently, Victors contains 5296 VFs obtained via manual annotation from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
102
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 137 publications
(108 citation statements)
references
References 35 publications
0
102
0
Order By: Relevance
“…We aimed to identify upregulated genes in both BMD761 and induced LD2 compared with naïve LD2 that may explain the phenotypic difference. Focussing on genes which were experimentally known to be associated with virulence 17 , we identified 17 up-regulated virulence genes in both BMD761 and induced LD2 relative to naïve LD2 (Supplementary Table S3). Specfically, we found that QSP1, which encodes a secreted peptide that has previously been implicated in quorum sensing and the upregulation of virulence of C. neoformans , was significantly downregulated in both the highly virulent BMD761 isolate and the induced environmental isolate versus its naïve self (Supplementary Table S3) 18 .…”
Section: Resultsmentioning
confidence: 99%
“…We aimed to identify upregulated genes in both BMD761 and induced LD2 compared with naïve LD2 that may explain the phenotypic difference. Focussing on genes which were experimentally known to be associated with virulence 17 , we identified 17 up-regulated virulence genes in both BMD761 and induced LD2 relative to naïve LD2 (Supplementary Table S3). Specfically, we found that QSP1, which encodes a secreted peptide that has previously been implicated in quorum sensing and the upregulation of virulence of C. neoformans , was significantly downregulated in both the highly virulent BMD761 isolate and the induced environmental isolate versus its naïve self (Supplementary Table S3) 18 .…”
Section: Resultsmentioning
confidence: 99%
“…The data were also clustered by using k-means with 1,723 genes (k = 4) (iDEP). We classified the DEGs into functional categories based on the bacterial bioinformatics database and analysis resource PATRIC (www.patricbrc.org) [65], which is integrated with information from VFDB (http://www.mgc.ac.cn/VFs/) [66], Victors [67], subsystems technology toolkit ( RASTtk ) [68, 69], and KEGG map [70]. Genes were also classified into pathways based on BioCyc database [71].…”
Section: Methodsmentioning
confidence: 99%
“…If these essential/virulence-associated epitopes are not targeted, there is high risk of epitope masking or switching, leading to rapid circumvention of the monoclonal therapy. Specialized resources such as PATRIC, VFDB, and Victors (41)(42)(43) compile virulence factors at the species level from dedicated research reports.…”
Section: Design Of Anti-virulence Mabs Using Functional Informationmentioning
confidence: 99%